Rheum australe: an Endangered High-Value Medicinal Herb of North Western Himalayas - Bhardwaj, Ravi; Sood, Meenu (International Journal of Economic Plants, 2022)
Rheum australe, a medicinal herb of therapeutic potential has been extensively used as a source of medicine since antiquity to cure a broad range of ailments without any documented adverse effects. The available scientific literature on this plant species, as presented in this review, reveals that it is an important medicinal plant used in a wide range of ethnomedical treatments across borders as also mentioned in different traditional systems of medicine, including Ayurveda, Homeopathic, Tibetan, Unani and Chinese systems. Moreover, the plant species is a rich reservoir of some major phytoconstituents, particularly anthraquinones, with well-known pharmacological efficacy against a spectrum of health ailments.